Presentation, diagnostic assessment and surgical outcomes in primary hyperparathyroidism: a single centre's experience. Issue 10 (October 2018) - Reid, Laura J; Muthukrishnan, Bala; Patel, Dilip; Crane, Mike S; Akyol, Murat; Thomson, Andrew; Seckl, Jonathan R; Gibb, Fraser W
Abstract : Objective: Primary hyperparathyroidism (PHPT) is a common reason for referral to endocrinology but the evidence base guiding assessment is limited. We evaluated the clinical presentation, assessment and subsequent management in PHPT. Design: Retrospective cohort study. Patients: PHPT assessed between 2006 and 2014 ( n = 611) in a university hospital. Measurements: Symptoms, clinical features, biochemistry, neck radiology and surgical outcomes. Results: Fatigue (23.8%), polyuria (15.6%) and polydipsia (14.9%) were associated with PHPT biochemistry. Bone fracture was present in 16.4% but was not associated with biochemistry. A history of nephrolithiasis (10.0%) was associated only with younger age ( P = 0.006) and male gender ( P = 0.037). Thiazide diuretic discontinuation was not associated with any subsequent change in calcium ( P = 0.514). Urine calcium creatinine clearance ratio (CCCR) was <0.01 in 18.2% of patients with confirmed PHPT. Older age ( P < 0.001) and lower PTH ( P = 0.043) were associated with failure to locate an adenoma on ultrasound (44.0% of scans). When an adenoma was identified on ultrasound the lateralisation was correct in 94.5%. Non-curative surgery occurred in 8.2% and was greater in those requiring more than one neck imaging modality (OR 2.42, P = 0.035). Conclusions: Clinical features associated with PHPT are not strongly related to biochemistry. Thiazide cessation does not appear to attenuate hypercalcaemia. PHPT remains the likeliest diagnosis in the presence of low CCCR. Ultrasound is highly discriminant when an adenoma is identified but surgical failure is more likely when more than one imaging modality is required.